The Accumulative Capacity of Pinus brutia and Cupressus sempervirens to Lead (Pb) and Zinc (Zn) - Nesafi, Ibrahim; Ibrahim, Dena (Latakia University Journal -Biological Sciences Series, 2013)
This study aims to investigate the abilities of two tree species (Pinus brutia and Cupressus sempervirens) planted in Banias Refinery Company to absorb and accumulate lead and zinc basically emitted by the Refinery. Samples of the planted species (leaves, bark, and wood) and soil from around the plants were collected and analyzed by atomic absorption spectrophotometer. The results did not show significant pollution with these two elements. Moreover, there were not any significant differences between the two species in terms of the accumulation of Pb and Zn. While the Pb concentrations ranged between (24.96-30.84 ppm) for P. brutia and (24.05-30.23 ppm) for C. sempervirens, the Zn concentrations ranged between (34.99-82.99 ppm) for P. brutia, (18.11-59.86 ppm) for C. sempervirens. It was also revealed that P. brutia bark accumulated Pb more than the other parts, whereas C. sempervirens leaves accumulated Zn more than the other parts.